Future perspectives in pulmonary arterial hypertension. (December 2016) - Simonneau, Gérald; Hoeper, Marius M.; McLaughlin, Vallerie; Rubin, Lewis; Galiè, Nazzareno
While there have been advances in the field of pulmonary arterial hypertension (PAH), disease management remains suboptimal for many patients. The development of novel treatments and strategies can provide opportunities to target other mechanisms that play a role in the complex pathobiology of PAH outside of the three main pathophysiological pathways. In this review, we highlight some of the potential PAH therapies or techniques that are being, or have been, investigated in phase II clinical trials. This review also discusses potential points for consideration in the development of novel therapies that target putative disease mediators or modifiers. Novel therapies and well-designed trials are important for improving the management of PAH patients http://ow.ly/YHPY304XdvH